Economic mechanisms for the transition to a "green" economy (Eurasian Journal of Ecology, 2016)
The author emphasizes the special importance of research issues related to the major environmental challenges, where the emphasis is on the fact that the consequence of the rapid development of the modern world economy has become almost uncontrollable increasing consumption of natural resources. The paths of leveling the set problems.
Keywords: the global economy; environment; ecosystems